2017
DOI: 10.1371/journal.pone.0185457
|View full text |Cite
|
Sign up to set email alerts
|

The burden of alcohol-related morbidity and mortality in Ottawa, Canada

Abstract: ObjectivesAlcohol-related morbidity and mortality are significant public health issues. The purpose of this study was to describe the prevalence and trends over time of alcohol consumption and alcohol-related morbidity and mortality; and public attitudes of alcohol use impacts on families and the community in Ottawa, Canada.MethodsPrevalence (2013–2014) and trends (2000–2001 to 2013–2014) of alcohol use were obtained from the Canadian Community Health Survey. Data on paramedic responses (2015), emergency depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…SRH is an inherently holistic measure and previous qualitative research conducted in Canada indicated that alcohol use is associated with many social activities [43]. Therefore, it is possible that women drink more for social reasons and perceive health benefits from the associated social networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRH is an inherently holistic measure and previous qualitative research conducted in Canada indicated that alcohol use is associated with many social activities [43]. Therefore, it is possible that women drink more for social reasons and perceive health benefits from the associated social networks.…”
Section: Discussionmentioning
confidence: 99%
“…In an Ottawa study, only 56% of respondents were concerned or strongly concerned about binge drinking; it was selected least frequently among alcohol-related concerns to be addressed first. Of those who cited binge-drinking as a concern, this concern was attributed to worries centered on individual risk, vulnerability to violence, and risk of future addiction [43].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially life-threatening complications of BN include gastrointestinal, endocrine and renal disturbances which can lead to severe electrolyte derangements and cardiac arrhythmias [25]. Among others, important factors contributing to the increased risk of suicide in people with BN could be the high level of impulsiveness [26], hopelessness [28] and-as already mentioned-comorbidities such as SUDs, PDs and ADs, like unipolar depression [28], which themselves are also associated with increased mortality [7][8][9][10][11][12][13][14][29][30][31][32][33]. In the literature, SUDs, PDs, ADs, and anxiety disorders were found the most frequent mental disorders comorbid to BN [34][35][36].…”
Section: Mortality In Bnmentioning
confidence: 99%
“…In this study, comorbid PD was found related to a worse treatment outcome. Potential comorbidities of AN including addiction to alcohol [15,16] or illicit drugs [17], unipolar depression [18] and PD [19] have been found to be associated with increased mortality. In a recent retrospective Swedish register study investigating mortality in women with AN, SUDs and depression significantly contributed to mortality, but not PDs [20].…”
Section: Mortality For People With Anmentioning
confidence: 99%